Calcium Signaling in the Ventricular Myocardium of the Goto-Kakizaki Type 2 Diabetic Rat - L. Al Kury; M. Smail; M. A. Qureshi; V. Sydorenko; A. Shmygol; M. Oz; J. Singh; F. C. Howarth (Journal of Diabetes Research)
The association between diabetes mellitus (DM) and high mortality linked to cardiovascular disease (CVD) is a major concern worldwide. Clinical and preclinical studies have demonstrated a variety of diastolic and systolic dysfunctions in patients with type 2 diabetes mellitus (T2DM) with the severity of abnormalities depending on the patients’ age and duration of diabetes. The cellular basis of hemodynamic dysfunction in a type 2 diabetic heart is still not well understood. The aim of this review is to evaluate our current understanding of contractile dysfunction and disturbances of Ca2+ transport in the Goto-Kakizaki (GK) diabetic rat heart. The GK rat is a widely used nonobese, nonhypertensive genetic model of T2DM which is characterized by insulin resistance, elevated blood glucose, alterations in blood lipid profile, and cardiac dysfunction.